2014
DOI: 10.1080/15528030.2014.880773
|View full text |Cite
|
Sign up to set email alerts
|

“It’s a Consolation”: The Role of Christian Religion for People With Dementia Who Are Living in Care Homes

Abstract: Little is known from the perspectives of people with dementia living in care homes regarding the role of faith in their lives. The study aimed to understand the impact the participants' faith has on their present lives. Ten people with moderate dementia who lived in four care homes were interviewed and the data analyzed using Interpretative Phenomenological Analysis. The results highlight the importance of faith in the participants' lives and point to supporting them to maintain their faith practices and tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Persons with other religions or life views of course also need spiritual care adopted to their needs. Nursing home residents with moderate dementia expressed that religion is consolation for them (109). Persons with advanced dementia need consoling care (69,110).…”
Section: Spiritual and Consoling Care At The End Of Lifementioning
confidence: 99%
“…Persons with other religions or life views of course also need spiritual care adopted to their needs. Nursing home residents with moderate dementia expressed that religion is consolation for them (109). Persons with advanced dementia need consoling care (69,110).…”
Section: Spiritual and Consoling Care At The End Of Lifementioning
confidence: 99%
“…(Higgins 2014;Keenan 2017aKeenan , 2017bNMBI 2014). For example, within Ireland, the nurse has a legal obligation to support the spiritual needs of care recipients' (NMBI 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Higgins (2014), in a qualitative study among residents of a UK care home living with advanced dementia, found that religion played an important role in maintaining an individual's identity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While it is difficult to define and measure spirituality, researchers have found that a sense of transcendence, of being part of something beyond the self , and finding meaning in life contribute to older people's sense of well‐being. In the West, those with a Christian faith make an easier adjustment to dementia . In addition, a systematic review has indicated that being religious, in any way, slows down cognitive decline and provides coping strategies .…”
Section: Religion and Spiritualitymentioning
confidence: 99%